International Monetary Fund Annual Report 1967. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1967)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1967. The report highlights that in 1966, industrial production and international trade on a worldwide basis expanded substantially. However, the slowdown in the tempo of economic activity in major industrial countries during the latter part of 1966 continued in the first half of 1967, and was accompanied by a shift of national economic policies toward expansion. Weakening of demand conditions in the industrial world served to ease inflation strains.